Open innovation analysis of the penta helix electric bus collaboration: Advancements in sustainable energy and engineering - Putri, Hawraul Insiyyah Sembodo (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: This research aims to analyze the application of the Open Innovation concept in the Penta Helix collaboration on the electric bus project at the Faculty of Engineering, Universitas Indonesia. The Penta Helix model involves five main actors: Academia, Industry, Government, Mass Media, and Society. This research employs a case study approach focusing on the Faculty of Engineering, Universitas Indonesia as the research object. Method: Data was collected through in-depth interviews, literature reviews, and document analysis. This approach was used to examine the collaboration's dynamics and the development process of the electric bus technology. Finding: The results indicate that the collaboration between the university and industry successfully developed an innovative and sustainable electric bus technology, complying with government standards. Academia plays a role in research and technology development, industry supports with financial resources and market access, government provides regulations and policy support, mass media disseminates information, and society offers feedback and technology adoption. Conclussion: The main challenges faced in this collaboration include stakeholder coordination and aligning the objectives of each actor. Additionally, cultural differences and expectations between the university and industry also pose barriers. Nevertheless, this research finds. that effective synergy among the five actors can accelerate innovation and provide significant economic and social benefits. This research is expected to contribute to the development of university-industry collaboration in Indonesia and enrich the literature on Open Innovation. Novelty/Originality of this Study: This study offers insights into how the Penta Helix collaboration model can drive innovation in the electric bus sector, highlighting the synergy between academia, industry, government, mass media, and society in the context of Open Innovation in Indonesia.